Natural fiber-reinforced composites thermal properties and applications - Krishnasamy, Senthilkumar (Wiley-VCH, 2022)
Natural Fiber-Reinforced Composites In-depth overview of thermal analysis of natural fiber-reinforced composites In Natural Fiber-Reinforced Composites: Thermal Properties and Applications, a team of distinguished researchers has delivered a comprehensive overview of the thermal properties of natural fiber-reinforced polymer composites. The book brings together information currently dispersed throughout the scientific literature and offers viable and environmentally friendly alternatives to conventional composites. The book highlights the thermal analysis of natural fiber-reinforced composites with techniques such as Thermogravimetric Analysis, Dynamic Mechanical Analysis, Thermomechanical Analysis, Differential Scanning Calorimetry, etc. This book provides: A thorough review of the thermal characterization of natural fiber-based hybrid composites Detailed investigation of the thermal properties of polymer composites reinforced with various natural fibers such as flax fiber, pineapple leaf fiber, sisal, sugar palm, grass fiber and cane fiber Discussions on the thermal properties of hybrid natural fiber-reinforced composites with various thermosetting and thermoplastic polymers Influence of nanofillers on the thermal stability and thermal decomposition characteristics of the natural fiber-based hybrid composites Natural Fiber-Reinforced Composites: Thermal Properties and Applications is a must-read for materials scientists, polymer chemists, and professionals working in the industry. This book is ideal for readers seeking to make an informed decision regarding materials selection for applications involving thermal insulation and elevated temperature. The suitability of natural fiber-reinforced composites in the automotive, mechanical, and civil engineering sectors is highligted.
Includes bibliographical references and index. - Online resource; title from PDF title page (John Wiley, viewed January 3, 2022)
Keywords: Fibrous composites -- Thermal properties; Composites à fibres; Propriétés thermiques; Fibrous composites; Thermal properties